PERBANDINGAN KADAR VITAMIN C PADA DAUN KELOR (Moringa oleifera) YANG TUMBUH DI DATARAN RENDAH, DATARAN RENDAH MENENGAH, DAN DATARAN TINGGI - Ratih Purwanti (Jurnal Permata Indonesia, 2022)
Moringa plant known as medicinal plant by using all part of tree start from leaf, bark, seed, until root. Nutrients contained in moringa plant is protein, β-caroten, vitamin c, minerals, especially iron and calcium. Vitamin c has keeping body fitness and prevent various types of disease. The Purpose to Know the comparison of vitamin c levels in moringa leaves (Moringa oleifera L) that grow in the lowlands, middle lowland, and highlands. Method of this research is an experimental research using one-shot case study desain. Object of the research is young moringa leaves taken from lowlands (2,5 MASL), middle lowland (325 MASL), and highlands (823 MASL) taken by cluster sampling to determine the area to be taken and proportionate stratified random sampling to determine leaves used. The independent variable is difference in the height of the place to grow. The dependent variable is comparison of vitamin c in moringa leaves (Moringa oleifera L). Statistical analysis using SPSS one way anova variation. Result highest level of vitamin c until lowest is young moringa leaves (Moringa oleifera L) from highlands (0,3252%), middle lowland (0,1951%), lowlands (0,0975%). Highest level of vitamin c is moringa leaves (Moringa oleifera L) from highlands. In future research, other methods of determining vitamin c levels can be carried out. Keyword : Moringa plant, Vitamin C, Grown